Axes of Formation: A Model for Assessing Theories of Spiritual Formation. Issue 2 (November 2019) - Gruenberg, Jeremiah; Asumang, Annang
The proliferation of theories of spiritual formation necessitates versatile tools for their assessment so as to achieve a degree of desirable standardization in the field. Empirically, the ideal assessment tool should be ecumenically applicable, receptive to interdisciplinary approaches, biblically grounded, theologically sound, and comprehensive in scope. This article outlines a four-axis model to be used for assessment of major elements of any spiritual formation theory. Assessment along the four axes evaluates a theory's goal, its integrative paradigmatic concept, its theological depth, and its proposed formational activities. The utility of the proposed model is illustrated by critically engaging an account of spiritual formation given by N. T. Wright. By breaking down a theory of spiritual formation into four axes, that theory's strengths and weaknesses are more readily addressed, and further, comparisons between theories may be made in a more consistently compatible manner.